Pollinating through art: creating public art to restore pollinator habitats and revitalize urban communities - Harris, Alexandria (Kansas State University, 2022)
The decline of pollinators and their habitats is a pressing issue worldwide. Over the past 30 years, beekeepers worldwide have recorded unusually high bee population losses (Oldroyd, 2007). Due to this decline, there is a need to increase pollinator habitats in urban areas; however, due to road infrastructure, manicured lawns, and urban development, there is little space to be utilized as restorative pollinator habitats (Sikora et al, 2020; Vaughan and Black, 2008). While colony collapse disorder in European honey bees has been explored widely in recent years, there is little research on how public art installations could address native bees and other pollinator declines in urban areas (Berenbaum, 2014). By examining creative ways to combine pollinator habitat and public art, this study aims to address the decline in native bees and other pollinators and their habitats by considering pollinator art in an ecological context through research-based design. The pollinator art created for this study integrates native plants and site context factors into hypothetical public art installations within Southeast Brush Creek, a high-vacancy area in Kansas City, Missouri. By designing functional art installations at different scales, for a typology of sites, this study examines: 1) How entomology research contributes to the form and materiality of public art as habitat. 2) How public art can revitalize pollinator habitats in urban settings. 3)How knowledge of native bees can inform the design of pollinator art for bee health and ease of maintenance. A literature review was used to develop an evidence-based framework that informs the designs of pollinator public art that could be incorporated into specific sites in the Brush Creek neighborhood in Kansas City, MO. The findings of this study offer insight into how research can creatively inform design solutions and be translated into public art that functions as a pollinator habitat. Pollinator art is an artistic tool that has the power to change the fabric of urban areas in a positive manner. This study contributes to the existing literature on the restoration and conservation of pollinator habitats with a broader outcome that highlights the potential implementation of pollinator art in a typology of urban settings.
Keywords: Pollinators; Art; Public art; Research-based design; Habitat restoration; Tactical urbanism; Urban acupuncture